Impact of large class on teaching learning at the primary school of Bangladesh - A. K. M. Obaydullah, Dr.; Shahnewaz, Md. (SPC Journal of Education, 2020)
Each Large classes teachers faces challenges everyday diversity of scholars , lack of flexibility, class environment management, difficulty of setting and enforcing classroom behavior, minimum attention to students, limited monitoring of students' learning and difficulty in engaging students to activities. The main assumption of this study is that effective teaching and producing learning is critically constrained by the large size of classes. Therefore the students' perception about large classes is negative. This research is to interact during a study of the effectiveness of educational science for big classes. The baseline of our study is predicated on data that has been collected from students' survey. The study was conducted throughout the 40 government primary school in Gazipur district of Bangladesh. During this study are observed the students' expectations, motivation, own perception on performance, views and preferences about the delivery of the lecture and therefore the learning. It was designed the study to detect accurately the maximum amount as possible students' attitude towards learning. Each student's responses, like the students own perception has been correlated to real performance as measured, weekly class work, quizzes, tutorials In this study will focuses other solutions to the above obstacles to conducting an efficient learning environment. The lecturing time and the mode of teaching both are investigated, and reviewed as a possible solution the issues encountered during the lecture. It compared the findings to the prevailing literature and other teachers' experiences. Studying students’ experience is sort of challenging. It may be used as a top quality indicator additionally to the quality in education. Evaluating students’ experience, need and expectations can cause improvements in teaching performance and achieving learning outcomes. Finally, there'll be a discussion of the problems raised and therefore the implications of those for various stakeholders in developing countries.